Retromandibular transparotid approach for subcondylar mandibular fractures: A retrospective study - VAROL, ALTAN; GÖÇMEN, GÖKHAN; ATALI, ONUR (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2016)
BACKGROUND: The aim was to evaluate the effectiveness and complications of retromandibular transparotid approach performed for the reduction of dislocated subcondylar fractures. METHODS: Fourteen patients with subcondylar mandibular fractures were evaluated (8 male, 6 female, age range 19-43 years). The primary predictor variable in the present study was time (preoperative vs postoperative). The primary outcome variables were inflammatory complication, facial nerve deficit (House and Brackmann classification), and presence of parotid fistula. The secondary outcome variables were occlusal disturbances, maximal interincisal opening (MIO), and temporomandibular joint (TMJ) pain (VAS). RESULTS: Excellent occlusion and function was observed postoperatively. One salivary fistula occurred after surgery but was healed after 3 weeks. No inflammatory complication was observed. Three patients had grade III and one patient had grade II facial nerve deficit, all recovered in 6 weeks. All patients were free of pain and no malocclusion was observed. MIO was ranging from 34 to 58 mm (mean 44.4 mm) after 6 months. CONCLUSION: The retromandibular transparotid approach is feasible and safe. It facilitates reduction and fixation of subcondylar fractures with functional outcomes and rare complications.
Keywords: Internal fixation; open reduction; retromandibular; subcondylar; transparotid; OPEN REDUCTION; INTERNAL-FIXATION; CONDYLE FRACTURES; SURGICAL-TREATMENT; RIGID FIXATION